RHYTMIC EXPERIMENTATION WITH RECYCLED MATERIALS: A CULTURAL AND ECOLOGICAL STUDY OF BANDUNG’S PERCUSSION - Mohamad Rudiana (SOSIOEDUKASI, 2025)
This study examines the creative practices of experimental percussion communities in Bandung that utilize found and recycled objects as sound-producing instruments. The research aims to understand how these communities explore, modify, and construct rhythms from non-conventional materials, and how their creativity is shaped by social interaction, aesthetic values, and environmental awareness. Using a qualitative approach through participant observation and in-depth interviews with community members, artists, and instrument makers, the study reveals that the transformation of discarded objects into percussion instruments generates unique sound innovations and fosters strong communal solidarity. The practice also creates an alternative cultural space where creativity, collaboration, and ecological consciousness intersect. Furthermore, experimentation with recycled objects functions as an expressive, educational, and environmentally engaged artistic medium. These findings demonstrate that recycled-based experimental percussion plays a significant role in shaping Bandung’s contemporary art ecosystem and promoting sustainable creative practices.